Understanding Farmer and Government Measure in Rat Pests Control in Rice Fields - Thuy Xuan; Tiuen Yen; Tuyet Caugh (Newinera Publisher, 2021)
This paper discusses the control of rat pets through highlighting its population growth, ecosystem, types and possible mechanism to use. During extended periods of fallow, rice field rats tend to congregate in escape places (refuge regions) such as bushes, yards, or rice warehouses. Rice plants suffered damage equivalent to five times their feeding requirements when rats were present. Rats damage plants from the tiller stage to the maximal tiller stages by devouring the growth point and the soft base of the stem while leaving the other portions of the plant unharmed. Without intensive control efforts (since the start of MT1), the rat population density on MT2 is confirmed to be higher and poses a serious threat to the success of MT2 harvesting. In one rice growing season, there is one population peak so in the rice-paddy-fallow cropping pattern there are two (2) population peaks.